Digitalisasi Cagar Budaya Kota Pekanbaru menggunakan web - Harun Mukhtar; Januar Al Amien; Muhammad Ilham Akbar; Hasanatul Fu'adah Amran (Unversitas Muhammadiyah Riau, 2022)
Recognition of cultural heritage and its preservation raises innovative ideas for digitizing. Digitization began to be discussed as an alternative solution to solving the problem of cultural heritage. Pekanbaru has a cultural heritage that includes buildings, artifacts, and structures. The cultural heritage found in the city of Pekanbaru started from the time of the Siak Kingdom, including the Railway Monument, Sultan Siak Shelter House, Ground Zero Pekanbaru, Red and White Monument, Marhum Pekan Tomb Complex, Pekanbaru Great Mosque, Surau Al Irhash, Tuan Khadi Shelter and Havenmaster's house. This study is intended to digitize the crocodile reserve in the city of Pekanbaru using the PHP and MySql programming languages ​​as data storage. The results of this study contribute to the preservation and recognition of cultural heritage as the nation's heritage. With the existence of a website about cultural heritage, this cultural heritage will not be forgotten by the masses.